Tensile and bending fatigue of the adhesive interface to dentin - Belli, Renan; Baratieri, Luiz Narciso; Braem, Marc; Petschelt, Anselm; Lohbauer, Ulrich (Dental Materials, 2010)
Objectives: The aim of this study was to evaluate the fatigue limits of the dentin-composite interfaces established either with an etch-and-rinse or an one-step self-etch adhesive systems under tensile and bending configurations. Methods: Flat specimens (1.2 mm × 5 mm × 35 mm) were prepared using a plexiglass mold where dentin sections from human third molars were bonded to a resin composite, exhibiting the interface centrally located. Syntac Classic and G-Bond were used as adhesives and applied according to the manufacturer's instructions. The fluorochrome Rhodamine B was added to the adhesives to allow for fractographic evaluation. Tensile strength was measured in an universal testing machine and the bending strength (n = 15) in a Flex machine (Flex, University of Antwerp, Belgium), respectively. Tensile (TFL) and bending fatigue limits (BFL) (n = 25) were determined under wet conditions for 104 cycles following a staircase approach. Interface morphology and fracture mechanisms were observed using light, confocal laser scanning and scanning electron microscopy. Statistical analysis was performed using three-way ANOVA (mod LSD test, p < 0.05). Results: Tensile and bending characteristic strengths at 63.2% failure probability for Syntac were 23.8 MPa and 71.5 MPa, and 24.7 MPa and 72.3 MPa for G-Bond, respectively. Regarding the applied methods, no significant differences were detected between adhesives. However, fatigue limits for G-Bond (TFL = 5.9 MPa; BFL = 36.2 MPa) were significantly reduced when compared to Syntac (TFL = 12.6 MPa; BFL = 49.7 MPa). Fracture modes of Syntac were generally of adhesive nature, between the adhesive resin and dentin, while G-Bond showed fracture planes involving the adhesive-dentin interface and the adhesive resin. Significance: Cyclic loading under tensile and bending configurations led to a significant strength degradation, with a more pronounced fatigue limit decrease for G-Bond. The greater decrease in fracture strength was observed in the tensile configuration. © 2010 Academy of Dental Materials.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Adhesive interface; CLSM; Cyclic fatigue; Dentin bonding; Flexural strength; Fracture; Tensile strength